THE VIRTUAL UNIVERSITY MODEL AS THE MAIN PLATFORM FOR IMPLEMENTATION OF PROFESSIONAL RETRAINING PROGRAM FOR TEACHERS BY THE EXMPLE OF SYRIAN VIRTUAL UNIVERSITY - K. O. Prosyukova (Science and Innovation Center Publishing House, 2014)
The interest in virtual education has recently increased in educational environment. Researchers in their scientific activity are focused on the benefits of the “virtual university” or “virtual college” models. But the range of a “virtuality” concept is too wide: some researchers recognize all information technologies in education as virtual means, while the others are looking for the ways to replace education in its general meaning with virtual educational space. The problem of virtual education is also relevant because the application area is boundless: school education, secondary professional education, higher education, training and retraining programs. Thus virtual education is able to become not only the innovative educational model, but also a possible solution to the problem of continuing education. One of the most successful examples in this field is the example of Syrian Virtual University, which has become the pioneer in virtual education in the Middle East region.